2005
DOI: 10.1126/science.1118919
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Synthesis of a Radiolabeled Imaging Probe Using Integrated Microfluidics

Abstract: Microreactor technology has shown potential for optimizing synthetic efficiency, particularly in preparing sensitive compounds. We achieved the synthesis of an [ 18 F]fluoride-radiolabeled molecular imaging probe, 2-deoxy-2-[ 18 F]fluoro- d -glucose ([ 18 F]FDG), in an integrated microfluidic device. Five sequential processes—[ 18 F]fluoride concentration, water evaporation, radiofluorination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
362
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 475 publications
(367 citation statements)
references
References 18 publications
1
362
1
3
Order By: Relevance
“…One [15], our group demonstrated release into~12 μL volume [49], and Lebedev et al [17] and Bejot et al [50] demonstrated release into 44 μL volume. This approach can be integrated with microfluidics by using packed-tubing cartridges [15], functionalized porous polymer monoliths [51], packed microchannels [52], or resinfilled inserts [12].…”
Section: Radioisotope Concentrationmentioning
confidence: 92%
See 3 more Smart Citations
“…One [15], our group demonstrated release into~12 μL volume [49], and Lebedev et al [17] and Bejot et al [50] demonstrated release into 44 μL volume. This approach can be integrated with microfluidics by using packed-tubing cartridges [15], functionalized porous polymer monoliths [51], packed microchannels [52], or resinfilled inserts [12].…”
Section: Radioisotope Concentrationmentioning
confidence: 92%
“…Microvalves [19], Copyright © 2013 Elsevier, Inc.) (g) EWOD chip with reaction volume ranging from 2 to 17 μL were used to close the reactor during reaction steps, and the permeability of the PDMS enabled escape of vapor for solvent exchange processes. By scaling up the reactor volume to 5 μL, it was possible to produce mCi amounts of [ 18 F]-labeled tracers [15]. Unfortunately, due to adverse interaction of PDMS with [ 18 F]fluoride [16], radioactivity losses were high and reliability was low.…”
Section: Platforms For Microliter Volume Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6] It has been shown that multiple droplets can be individually addressed in an open oil chamber using physically patterned electrodes, although complex wiring and interconnection issues arise for addressing numerically large droplet arrays. 9,10 To solve this problem, a microfluidic device integrating a high voltage complementary metal-oxide semiconductor driving circuit recently achieved active and parallel droplet control. However, this approach increases the fabrication cost of microfluidic devices, which are often preferred to be disposable.…”
mentioning
confidence: 99%